2020
DOI: 10.3390/su12104262
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Governance Affect the Quality of Integrated Reporting?

Abstract: This study examines how governance mechanisms affect the quality of integrated reporting (IR), which is fast emerging both as a tool to help firms understand their value creation process and to communicate effectively with external stakeholders. This study first developed an index to assess the quality of integrated reports. Subsequently, 132 integrated reports of Sri Lankan public listed companies selected over a three-year period were content analysed. The hypotheses formulated on the relationship between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
101
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 109 publications
(213 reference statements)
11
101
2
7
Order By: Relevance
“…As IR aims to explain to the providers of financial capital how an entity creates value over time, one of the main questions that arises is whether investors find integrated reports more decision-useful than traditional annual reports [4][5][6]. Although several studies have seemingly addressed this issue, they have only provided inconclusive and mixed results while being constrained by their choice of method and contextual setting.…”
Section: Introductionmentioning
confidence: 99%
“…As IR aims to explain to the providers of financial capital how an entity creates value over time, one of the main questions that arises is whether investors find integrated reports more decision-useful than traditional annual reports [4][5][6]. Although several studies have seemingly addressed this issue, they have only provided inconclusive and mixed results while being constrained by their choice of method and contextual setting.…”
Section: Introductionmentioning
confidence: 99%
“…Board characteristics The size of a board (number of board members) can signal managerial ability and expertise, which should improve the quality of information disclosure, and several studies support this view (Cooray and Senaratne 2020 ; Jizi et al 2014 ). Board size is also positively related to CSR (Endrikat et al 2020 ).…”
Section: Corporate Governance Mechanismsmentioning
confidence: 99%
“…Diversity (of gender, race, and experience) is also studied extensively, with studies investigating the impact of different characteristics of the board on firm performance. Gender diversity (usually measured as the proportion of women on boards) is argued to have a positive impact on the quality of voluntary disclosures including environmental disclosures (Cooray and Senaratne 2020 ; De Villiers 1998 ) and it is possible that gender diversity also contributes to the quality of corporate governance disclosures. Certainly research has found women to have a different attitude towards risk than men (Croson and Gneezy 2009 ).…”
Section: Corporate Governance Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations